THE PHILOSOPHICAL ESSENCE OF ILLNESS AND HEALTH (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article explores the philosophical essence of illness and health as fundamental categories in medical science and human existence. Health and disease are not only biological conditions but also complex phenomena shaped by social, psychological, cultural, and ethical dimensions. The study analyzes various philosophical perspectives on health and illness, including biomedical, holistic, and existential approaches. Special attention is given to the understanding of health as a dynamic state of physical, mental, and social well-being, and illness as a disruption of harmony within the individual and between the individual and society. The paper also highlights the role of values, perception, and human experience in defining these concepts. The findings suggest that integrating philosophical insights into medical education can enhance clinical thinking, improve doctor–patient relationships, and promote a more humanistic approach to healthcare.